Identidade docente nos cursos de Ciências Contábeis: estudo das IES do município de Fortaleza - Andrade, Joyce Arrais de Araújo (2012)
The undergraduate course in accounting has on its faculty from strong features of the labor market. Many of the teachers of this course work in other activities besides teaching higher education institutions, which may impair their dedication to teaching. Coupled with this reality, we have the quantitative expansion of graduate programs in Brazil, which causes some Higher education institutions do not worry about the quality of education offered only seeking profit, which ends up harming the teaching learning. This research aimed to investigate how the teachers of the Accountancy Courses of Higher Education Institutions in the city of Fortaleza identify themselves professionally, in order to realize the extent to which the identification of these professionals can reflect on their development as a teacher. It presents a history of the evolution of Science Degree in Accounting in Brazil and the accounting profession, and aspects of teacher training higher education in general and specifically the accounting as well as an approach to identity in teaching courses Accounting. The research is characterized as qualitative, descriptive using the procedures for bibliographical research and field. As an instrument of fieldwork used to interview. First survey was conducted on how many Higher education institutions offer Accounting Course in Fortaleza, after this identification is investigated which teachers graduated in accounting and charge of teaching technical subjects of accounting, which totaled 113 (one hundred and thirteen) teachers reflecting the amount of research subjects. Interviews were conducted in ten (10) higher education institutions Fortaleza, which were recorded and transcribed for analysis of results. At the end it was concluded that the identification of teachers from Accounting as a teacher or accountant is divided, confirming the conflict that exists between the two professions, caused by the strong appeal of the accounting profession and the exercise concurrent two professions by most teachers the course. Considering all aspects studied, it appears that the quality of higher education in accounting and valuation depends on the dedication of the teachers teaching.